Arguments for austerity, old and new: the British Treasury in the 1920s and the Bundesfinanzministerium in the 2010s - Fernando J. Cardim de Carvalho (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2018)
Much of the criticism directed at austerity programs implemented after the 2007/2008 financial crisis, more forcefully in the eurozone, have relied on the same arguments Keynes and others raised against the (British) Treasury View developed in the 1920s and 1930s. Austerity, however, has been proposed most insistently in the 2010s by European authorities, led by the German Federal Ministry of Finance, the Bundesfinanzministerium (BMF). While the arguments for austerity then and now share some common elements, there are enough original arguments being presented by the BMF to make many of the criticisms ineffective. The paper reconstructs both views, the Treasury's and the BMF's, to show and evaluate their similarities and their differences.
Keywords: E32; E62; E63; 330; fiscal policy; austerity; business cycles